THE SOCIAL MEDIA PHENOMENON: HOW INFLUENCERS SHAPE ADOLESCENT BEHAVIOR - Byrne, Liam Patrick; Murphy, Aoife Siobhan (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
Social media influencers (SMIs) have emerged as potent agents for brand promotion and awareness targeting specific demographics, notably adolescents. This study investigates the multifaceted influence of SMIs on adolescents' behaviors, attitudes, and communication patterns. Brands strategically collaborate with SMIs to tap into the popularity they hold among adolescents, utilizing them as conduits for product promotion and content dissemination. The captivating reach of SMIs among adolescents is attributed to their significant online presence and the resonance of their content with the young audience. Drawing upon research that underscores the extensive impact of digital influencers on adolescents, this study sheds light on the profound connection adolescents establish with SMIs. Beyond entertainment, these influencers are sought after for guidance, companionship, and advice, shaping the relational dynamics between adolescents and SMIs. This dynamic interplay is deeply ingrained in adolescents' daily routines, thereby warranting a comprehensive exploration of its dimensions. Notably, the journal Frontiers in Psychology has recently dedicated a volume to elucidate the pervasive role of SMIs in the lives of children and adolescents. The study's findings contribute to a nuanced understanding of how SMIs wield influence, particularly within the realm of adolescent behavior and decision-making. By examining the intricate relationship between adolescents and SMIs, this research offers insights into the evolving landscape of brand promotion and communication in the digital age.